Protein induced vitamin k absence(PIVKA-II) response in relation to treatment modalities among hepatocellular carcinoma patients at Hospital Universiti Sains Malaysia - Datoo, Adil Anvarali (2021)
Background: Hepatocellular carcinoma(HCC) is the commonest tumour of the liver with multiple aetiologies responsible for cirrhosis which evidently and eventually leads to hepatocellular carcinoma. With drastically increasing incidence since 1990 in Malaysia from 6.1 to 42.8% and with an annual mortality rate of 6.1%, the diagnosis of hepatocellular carcinoma is mainly dependent of imaging and biochemical markers. The commonest imaging modalities used to diagnose hepatocellular carcinoma are magnetic resonance imaging and computed tomography of the liver, while the commonest tumour marker used in conjunction with imaging is alpha-fetoprotein(AFP).In the setting of hepatocellular carcinoma, 30% of the time, the tumour marker alpha-fetoprotein is not elevated which leads to a conundrum during the time of diagnosis. A more robust tumour marker is required and PIVKA-II has shown potential in this regards with a few studies showing that PIVKA-II was superior in both sensitivity and specificity in the initial diagnosis, during follow up post treatment via hepatic artery embolization and hepatic artery infusion and it also shows a better correlation with overall survival in comparison to AFP. The purpose of this study is to evaluate the association between radiological response and PIVKA-II response among patients who undergo interventional radiological treatment, as radiological response is used as a bench mark to either proceed with more interventions or to observe the patients. Methods: A prospective study was conducted at Hospital Universiti Sains Malaysia(USM), Kota Bharu, Kelantan, Malaysia, where 66 patients who underwent interventional radiological treatment for hepatocellular carcinoma had blood investigation for PIVKA-II taken prior to the treatment, 6 weeks post treatment and 3 months post treatment with concurrent computed tomography or magnetic resonance imaging at baseline, 6 weeks post treatment and 3 months post treatment. Of the 66 patients, only 28 patients were available at the end of the 3rd month post intervention, this was due largely to the patients succumbing to their disease and partly due to the pandemic. The radiological response was based on modified response evaluation criteria(mRECIST) into four criteria’s of progressive disease, stable disease, partial response and complete response. PIVKA-II response was classified into either PIVKA-II responders or nonresponders. The association between radiological response and PIVKA response was carried out using Fischer exact test. Results: There was a significant association between radiological response and PIVKA-II response at 6 weeks post interventional radiological treatment with a P value of <0.001 and a Cramer’s V value of 0.71. However at 3 months post treatment, there was no significant association between radiological response and PIVKA-II response with a P value of 0.915 and Cramer’s V value of 0.141. Conclusion: The overall study shows that there was no significant association between post interventional radiological response at 3 months and PIVKA-II response and as of now, tumour marker PIVKA-II in itself cannot be a substitute for radiological imaging. However, it can be used in conjunction with imaging.